CAN-Catalyzed Rapid C–O Bond Formation towards α-Aminoxylation of Ketones - Feng, Peng; Song, Song; Zhang, Li-He; Jiao, Ning (Synlett, 2014)
A simple and efficient approach towards α-oxyaminated ketones has been developed through CAN-catalyzed C–O bond formation with 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO). The environmentally friendly transformation is practical due to the use of commercial available catalyst, easy operating procedures, the broad substrate scope, and short reaction time.
Keywords: CAN; ketone; α-aminoxylation; C–O bond formation; TEMPO